1989
DOI: 10.1021/bi00451a005
|View full text |Cite
|
Sign up to set email alerts
|

Substrate proton of the pyruvate kinase reaction

Abstract: The pyruvate kinase reaction occurs in separate phosphate- and proton-transfer stages: (formula; see text) K+, Mg2+, and Mg.ADP are known to be required for the phosphoryl transfer step, and K+ and Mg2+ with allosteric stimulation by MgATP are important for proton transfer. This paper uses the isotope trapping method with 3H-labeled water to identify the proton donor and determine when in the sequence of the catalytic cycle it is generated. When the enzyme was allowed to exchange briefly with 3H2O (pulse phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…On the other hand, only a relatively small amount of solvent hydrogen is found in the methyl groups of the leucine moiety. The biosynthesis of leucine from two molecules of pyruvate and one molecule of acetyl-CoA involves the introduction of one solvent hydrogen atom into each of the leucine methyl groups because of the transformation of phosphoenol pyruvate to pyruvate (11)(12)(13). Additional solvent hydrogen can be introduced into pyruvate by spontaneous proton exchange because of the relatively high acidity of the pyruvate methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, only a relatively small amount of solvent hydrogen is found in the methyl groups of the leucine moiety. The biosynthesis of leucine from two molecules of pyruvate and one molecule of acetyl-CoA involves the introduction of one solvent hydrogen atom into each of the leucine methyl groups because of the transformation of phosphoenol pyruvate to pyruvate (11)(12)(13). Additional solvent hydrogen can be introduced into pyruvate by spontaneous proton exchange because of the relatively high acidity of the pyruvate methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…No other side chain is within less than 5 A of His 373 N'. Thus, the topography at the active site does not appear to favor the existence of the kind of multiple proton pool such as was described for some enzymes that catalyze proton abstraction from carbon (Kuo & Rose, 1987;Rose & Kuo, 1989;Rose et al, 1990). The presence of a number of fixed water molecules at the active site of subunit S1 (no ligand present) might at first sight suggest the possibility of a water-mediated proton transfer.…”
Section: Extreme P K Displacements At Enzyme Active Sites 543mentioning
confidence: 93%
“…The ⑀-amino group of Lys-269 as the possible candidate for the acid/base catalyst in PK was supported by the measurement of multiple protons that are incorporated into pyruvate with rabbit muscle pyruvate kinase (10). Subsequent refined x-ray crystal structures of the yeast enzyme with bound phosphoglycolate (11) and of the rabbit muscle enzyme complexed with pyruvate (12) demonstrated that Lys-240 is at the 2-re face of the double bond of the enolate and is in apparent contact with the phosphoryl group of PEP.…”
mentioning
confidence: 98%